Mitigating Gender and Maternal and Child Health Injustices through Faith Community-Led Initiatives - Ikenna J. Nwakamma, MPH; Amber Erinmwinhe, BSc; Arinzechukwu Ajogwu, BSc; Aniekan Udoh, MPH; Anne Ada-Ogoh, MD (Global Health and Education Projects, Inc., 2019)
Background and Objective: Congregational Health Empowerment and Social Safety Advocates (CHESSAdvocates) initiative, a project aimed at mitigating maternal and child health (MCH) and gender injustices in religiously pluralistic societies, was implemented in two Northern Nigerian states of Benue and Kaduna between September 2018 and July 2019. The objective of this study was to assess the effectiveness, sustainability and factors of success in the CHESS-Advocates model as a faith community approach to mitigating gender and MCH injustices in Northern Nigeria. Methods: Data were from desk review of monthly project reports which were documented monthly all through the 10-month project life, and qualitative assessment conducted in July 2019 at the end of project. The assessments involved focus group discussions, key informant interviews, and in-depth interviews conducted in four randomly selected communities in each of the project states. The variables of interest were sustainability, effectiveness of initiative, and the factors that contributed to the success of the program. Results: The CHESS-Advocate model was effective in the mobilization of community response that improved uptake and acceptance of antenatal care (ANC), immunization, and uptake of human immunodeficiency virus (HIV) testing services. The model was cost-effective and able to instigate change in harmful practices, particularly in highly religious communities. The model showed promise of sustainability and identified some factors that led to its success in the different communities. Conclusion and Global Health Implications: The CHESS advocates model showed promises of efficacy in engaging faith communities as important actors in promoting MCH practices and mitigating gender injustices particularly in rural and underserved communities. Like other faith based models, the CHESS-Advocates model provided opportunities in faith congregations for building sustainable development in health and social justice. The model helped to improve MCH seeking behavior, influenced change in harmful gender norms and in community response against gender based violence in rural communities. Key words: • MCH • Gender justice • HIV • CHESS-Advocates • Faith • Northern Nigeria • Nigeria   Copyright © 2019 Nwakamma et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.